1000 events that shaped the world - O'Toole, Dan.; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2007)
Chronicles the historic events that have changed the world, ranging from the earliest form of life on Earth to the birth of many of today's modern technologies such as e-mail
Authors: Dan O'Toole ... [et al.]--P. 404
Includes bibliographical references (p. 402-403) and index
Keywords: History -- Outlines, syllabi, etc